Improving The Fine Motor Ability of Children With Cerebral Palsy Through Contextual Learning Based on Maze Game Media - Rachmat, Faisal; Yufiarti, Yufiarti; Jamaris, Martini; Mulyadi, Seto (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The Maze game media helps develop children's fine motor abilities, such as flexing fingers and wrists, and fine motor skills linked with the movement skills of both hands, as well as their capacity to combine eye senses and hand activity. This study aims to determine the increase in fine motor skills of children with cerebral palsy through a contextual learning model based on maze game media at 3 to 8 years old at SDLB Type D Disabled Children Foundation, South Jakarta. This research method uses action research. Action research is cycle-oriented research on various actions or interventions carried out by researchers as classroom teachers. The research took place from the design stage to the evaluation of practical classroom interventions regarding teaching and learning activities to enhance the fine motor skills of cerebral palsy-affected students. In the 2021-2022 school year, researchers studied children's fine motor abilities using maze game media. This research consists of three cycles (pre-cycle, cycle 1, and cycle 2). The results of this study indicate that the improvement of fine motor skills of children with cerebral palsy through media-based contextual models maze games are effectively negative or low inclined. This research implies that one of the creative ways to improve fine motor skills is through activities based on contextual learning models based on maze game media. In addition, using maze media can effective communication between class teachers and CP children so that CP children have better concentration and are independent in carrying out their fine motor movements at school and homeÂ